MANAGEMENT OF READING COMPREHENSION FROM THE TEACHING TASK OF EDUCATION: : A LOOK FROM VIRTUALITY - Piratoba, Nancy Omaira; Bracho Pérez, Kleeder (Revista Arbitrada Formación Gerencial, 2024)
Reading comprehension from the teaching activity and the appropriation of ICT as a fundamental process in the acquisition of contextualized knowledge in virtuality. It plays an indispensable role in reading and writing in the learning system, unquestionably, not only because it is a tool that allows the management of all areas of knowledge, but also because of its ability to produce and express thought. The research proposes an innovative plan for the development of reading comprehension in the teaching task from virtuality in fourth grade students of the Presbítero Álvaro Suarez Educational Institution of Villa del Rosario Norte de Santander Republic of Colombia, the specific objectives are: Identify the skills of reading comprehension in the teaching task of basic primary education from virtuality. Describe the pedagogical practice in the teaching task from virtuality. Generate an innovative plan for the development of reading comprehension in the teaching task from virtuality. The methodology guided by the quantitative approach, descriptive level and field design, the population consisting of 123, a total of 120 students and three teachers, the sample was represented by 40 students from section 01 and the three teachers for a total of 43, a survey was applied and the data was analyzed using graphs and statistical frequency tables. Finally, it follows that technological resources support pedagogical practice and motivate students' reading comprehension.